Literature Review: Optimizing Leaflets as a Medium for Health Information - Ayu Endang Purwati; Adelia Agustin; Deli Parida; Fatimah Khoirun Nisa; Siti Nurkholizah; Tita Tamala; Saskia Siti Khoerunisa (LPPM STIKes Muhammadiyah Ciamis, 2025)
Introduction: One of the main objectives of health development is to improve public health by focusing on preventive and promotive efforts, which cannot be separated from the role of health workers in providing education. The health education process will be delivered effectively with communication support accompanied by simple, interesting health information media and the use of easy-to-understand language. Information media plays an important role in the success of the health education process. Health information media that are widely used include electronic, digital, audiovisual, and print media, but not all people have access to them. Print media in the form of leaflets are information sheets that contain concise, compact, and systematic messages, accompanied by illustrations that appeal to readers. Optimizing leaflets as a medium for health information can help and encourage changes in health attitudes and behaviors. Objective: The main objective of this article is to optimize leaflets as a useful health information tool to increase knowledge, foster positive attitudes, and encourage changes in health behavior. Method: This study uses a literature review design to examine and analyze the results of previous studies relevant to the optimization of leaflets as a medium for health information. The data sources are scientific articles published in reputable national journals. Result: The results of this literature search were obtained from Google Scholar, PubMed, Science Direct, and Garuda. The criteria in this literature are articles that focus on discussing health information leaflets published from 2023 to 2025. Conclusion: Leaflets are an optimal medium for health information that can improve the knowledge and attitudes of the target audience.